The use of slang words in online learning context of EFL class - Rizky Lutviana; Siti Mafulah (Universitas Merdeka Malang, 2021)
Abstract During Covid-19 pandemic teachers and students in Indonesia adapt to continue learning by implementing online learning. Online learning creates a new way of communication between teacher and students in online classroom context. This way of communication makes both teacher and students employ new strategy in communication, one of which is by using slang words in online class. This study aimed at investigating the use of slang words by 34 EFL students in Translation online class during 1 semester. This study employed descriptive qualitative in which the source of data is the transcript of students’ chat in WhatsApp Group (WAG) during 6 months. Additionally, questionnaire was used to collect the data about students’ attitudes toward the use of slang words. It is found that students used 32 slang words from both English and Indonesian, most slang words used were influenced by popular slang words used in social media. Students mostly used slang words when (1) chatting with friends in discussing informal topic such as holiday, make up class, and connection problem; (2) expressing feeling; (3) addressing their friends’ names; (4) discussing lesson; (5) responding teacher’s question, and (6) greeting the teacher. Students’ attitude toward the use of slang was positive, they explained that they used slang words in online class to make learning atmosphere more alive and relaxed and those make them easier to understand the lesson. However, students limit the use of slang words when chatting with teacher, most students consider impolite to use slang words as freely as when they chatted with their classmates.online learning, slang words, EFL class